Optical laminate and image display device using same

By measuring and processing the three-dimensional data of the optical laminated body, optimizing the concave and convex shape of its surface, the problem of insufficient sliding properties in the prior art is solved, and an optical laminated body with both optical characteristics and sliding properties is realized, which is suitable for an image display device.

CN119234164APending Publication Date: 2024-12-31TOPPAN HOLDINGS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041418.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-20
Filing Date
2023-04-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing roughness parameters cannot effectively represent the sliding properties of the optical laminated body for displays with touch panels, especially the complex and random concave and convex shapes, which leads to the failure to meet the sliding properties requirements.

Method used

Measure the three-dimensional data of concave and convex shapes through optical interference or contact, perform fast Fourier transformation, calculate the average value of power spectrum intensity in a specific spatial frequency range, and meet specific A, B, and C conditions to optimize the optical stacked body The surface is concave and convex, thereby improving sliding.

Benefits of technology

An optical laminate with excellent optical characteristics and sliding properties is realized, and is suitable for image display devices, ensuring smoothness and low friction coefficient when fingers slide, and improving user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234164A_ABST
    Figure CN119234164A_ABST
Patent Text Reader

Abstract

Provided are an optical laminate having excellent optical characteristics and sliding properties, and an image display device using the same. The optical laminate is characterized in that the outermost surface of the optical laminate has an uneven shape, and the optical laminate satisfies the following conditions (1)-(3) at the same time. In the present invention, three-dimensional data of the height of the irregularities is obtained by measuring the irregularities by an optical interference method or a contact method, an image obtained from the three-dimensional data is subjected to frequency analysis by fast Fourier transform, and when the spatial frequency f is calculated, A: 0lt; f < = 100 cycle / mm, B: 100 cycle / mmlt; f < = 200 cycle / mm, C: 200 cycle / mmlt; f is an average value of the power spectrum intensity in the range of 300 cycle / mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body and an image display device using the same. Background Art

[0002] AG (anti-glare) films have an anti-glare layer with fine concavo-convex shapes on the surface, and the fine concavo-convex shapes suppress the reflection of external light by diffusing reflected light. In addition, it is also known that a low refractive index layer (LR) is stacked on the anti-glare layer to further suppress reflected light by optical interference, and AGLR films are used in various displays.

[0003] The anti-glare properties of AG film and AGLR film are mainly determined by the surface roughness of the anti-glare layer. In the past, the preferred surface roughness of the anti-glare layer was often expressed using the surface roughness parameters specified in ISO 25178 and the line roughness parameters specified in JIS B 0601 (see, for example, Patent Documents 1 to 3).

[0004] Furthermore, AG films and AGLR films used in displays with touch panels are required to have good sliding properties for fingers during operation in addition to anti-glare properties.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 5360616

[0008] Patent Document 2: Japanese Patent No. 5382034

[0009] Patent Document 3: Japanese Patent No. 6135131 Summary of the invention

[0010] Problems to be solved by the invention

[0011] The required slip properties of an optical laminate for use in a display with a touch panel vary depending on the concavo-convex shape of the outermost surface. Therefore, as a method for expressing the slip properties of an optical laminate, it is conceivable to use the above-mentioned roughness parameter and design an optical laminate with good slip properties based on the roughness parameter.

[0012] However, the above-mentioned existing roughness parameters cannot represent all random concavo-convex shapes and complex concavo-convex shapes. For example, the arithmetic mean height Sa specified in ISO 25178 is an indicator commonly used when evaluating surface roughness, but even if the Sa value is the same, the concavo-convex shape and sliding properties may be greatly different. Therefore, the previous roughness parameters are not suitable for representing sliding properties.

[0013] An object of the present invention is to provide an optical layered body having excellent optical properties and slidability, and an image display device using the same.

[0014] Means for Solving the Problem

[0015] The optical laminate of the present invention is characterized in that its outermost surface has an uneven shape and simultaneously satisfies the following conditions (1) to (3).

[0016] 20,000 ≤ A ≤ 300,000 (1)

[0017] 300 ≤ B ≤ 800 (2)

[0018] 10 ≤ C ≤ 180 (3)

[0019] Herein, when three-dimensional data of the uneven height obtained by measuring the uneven shape by an optical interference method or a contact method is transformed into first image data with the uneven height as a pixel value, and the first image data is transformed into a second image by a fast Fourier transform, and the spatial frequency f of the X coordinate of the power spectrum of the image in the range of ±20 Pixel in the positive X-axis and Y-axis directions passing through the origin in the second image is calculated.

[0020] A: The average value of the power spectrum intensity in the range of 0 < f ≤ 100 cycle / mm

[0021] B: The average value of the power spectrum intensity in the range of 100 cycle / mm < f ≤ 200 cycle / mm

[0022] C: The average value of the power spectrum intensity in the range of 200 cycle / mm < f ≤ 300 cycle / mm

[0023] The image display device of the present invention includes the above-described optical laminate.

[0024] Effects of the Invention

[0025] According to the present invention, it is possible to provide an optical laminate having excellent optical properties, appearance, and slidability, and an image display device using the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 FIG. is a cross-sectional view schematically showing an example of the optical laminate of the embodiment.

[0027] Figure 2 FIG. is a cross-sectional view schematically showing another example of the optical laminate of the embodiment.

[0028] Figure 3 FIG. is a diagram showing an evaluation method of antiglare property.

[0029] Figure 4 FIG. is a diagram showing an evaluation example of antiglare property. DETAILED DESCRIPTION OF THE INVENTION

[0030] Figure 1 This is a cross-sectional view schematically showing an example of the optical layered body according to the embodiment.

[0031] The optical laminate 11 includes a transparent support 2 and an antiglare layer 3 (AG layer) laminated on one surface of the transparent support 2. The optical laminate 11 is an optical film (also referred to as an "AG film") that scatters incident light by fine irregularities on the outermost surface to suppress reflection of external light.

[0032] The transparent support 2 is a film that becomes the base of the optical laminate 11, and is formed of a material with excellent visible light transmittance. As the forming material of the transparent support 2, polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyacrylates such as polymethyl methacrylate; polyamides such as nylon 6 and nylon 66; transparent resins or inorganic glass such as polyimide, polyarylate, polycarbonate, triacetyl cellulose, polyacrylate, polyvinyl alcohol, polyvinyl chloride, cycloolefin copolymer, norbornene-containing resin, polyether sulfone, and polysulfone can be used. The thickness of the transparent support 2 is not particularly limited, but is preferably set to 10 to 200 μm.

[0033] In order to improve adhesion with other laminated layers, the surface of the transparent support 2 may be subjected to surface modification treatment. Examples of surface modification treatment include alkali treatment, corona treatment, plasma treatment, sputtering treatment, application of a surfactant or silane coupling agent, and Si vapor deposition.

[0034] The antiglare layer 3 is a functional layer that forms the fine concavo-convex shape of the outermost surface of the optical layered body 11 .

[0035] The antiglare layer 3 is formed by applying a coating liquid containing an active energy ray-curable compound and organic fine particles and / or inorganic fine particles (filler) on the transparent support 2 and curing the coating film.

[0036] As the active energy ray-curable compound, for example, a monofunctional, difunctional, or trifunctional or higher (meth)acrylate monomer can be used. In addition, in this specification, "(meth)acrylate" is a general term for both acrylate and methacrylate, and "(meth)acryloyl" is a general term for both acryloyl and methacryloyl.

[0037] Examples of the monofunctional (meth)acrylate compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, and tert-butyl (meth)acrylate. Isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, benzyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phosphoric acid (meth)acrylate, ethylene oxide modified phosphoric acid (meth)acrylate, phenoxy (meth)acrylate, ethylene oxide modified phenoxy (meth)acrylate, propylene oxide modified phenoxy (meth)acrylate meth)acrylate, nonylphenol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, propylene oxide modified nonylphenol (meth)acrylate, methoxydiglycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acrylic acid adamantane derivative mono(meth)acrylates such as acryloyloxypropyl hydrophthalate, 2-(meth)acryloyloxypropyl hexahydrophthalate, 2-(meth)acryloyloxypropyl tetrahydrophthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, 2-adamantane, and adamantane acrylate having a monovalent mono(meth)acrylate derived from diamondoid, etc.

[0038] Examples of the bifunctional (meth)acrylate include di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and hydroxyvaleric acid neopentyl glycol di(meth)acrylate.

[0039] Examples of trifunctional or higher-functional (meth)acrylates include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris-2-hydroxyethyl isocyanurate tri(meth)acrylate, glycerol tri(meth)acrylate and the like tri(meth)acrylates, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, di(trimethylol)propane tri(meth)acrylate and the like tri(meth)acrylates. Polyfunctional (meth)acrylate compounds having three or more functions, such as compounds, pentaerythritol tetra(meth)acrylate, di(trimethylol)propane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, di(trimethylol)propane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and di(trimethylol)propane hexa(meth)acrylate, and polyfunctional (meth)acrylate compounds in which a part of the above (meth)acrylates is substituted with an alkyl group or ε-caprolactone.

[0040] In addition, as a multifunctional monomer, urethane (meth)acrylate can also be used. As urethane (meth)acrylate, for example, there can be mentioned a product obtained by reacting an isocyanate monomer or prepolymer with a polyester polyol, and then reacting the obtained product with a (meth)acrylate monomer having a hydroxyl group.

[0041] Examples of urethane (meth)acrylates include pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate isophorone diisocyanate urethane prepolymer.

[0042] The above-mentioned multifunctional monomer may be used alone or in combination of two or more. The above-mentioned multifunctional monomer may be a monomer in the coating liquid or an oligomer obtained by partial polymerization.

[0043] Organic particles are materials that mainly form fine concavo-convex on the surface of the anti-glare layer 3 and impart the function of diffusing external light. As organic particles, resin particles formed by light-transmitting resin materials such as acrylic resin, polystyrene resin, styrene-(methyl)acrylate copolymer, polyethylene resin, epoxy resin, silicone resin, polyvinylidene fluoride, polyvinyl fluoride resin can be used. In order to adjust the dispersion of the refractive index and the resin particles, two or more resin particles with different materials (refractive index) can also be used in combination.

[0044] The inorganic fine particles added to the anti-glare layer-forming composition are preferably nanoparticles having an average particle diameter of 10 to 200 nm.

[0045] Inorganic particles are materials mainly used to adjust the sedimentation and aggregation of organic particles in the anti-glare layer 3. As inorganic particles, silica particles, metal oxide particles, various mineral particles, etc. can be used. As silica particles, for example, silica particles surface-modified with reactive functional groups such as colloidal silica or (meth) acryloyl groups can be used. As metal oxide particles, for example, aluminum oxide, zinc oxide, tin oxide, antimony oxide, indium oxide, titanium oxide, zirconium oxide, etc. can be used. As mineral particles, for example, mica, synthetic mica, vermiculite, montmorillonite, iron montmorillonite, bentonite, beidellite, soapstone, hectorite, sphenestone, nontronite, magadiite, green dapoxetine, hydromonite, layered titanic acid, montmorillonite, synthetic montmorillonite, etc. can be used. The mineral particles can be any one of natural and synthetic (including substitution bodies and derivatives), or a mixture of the two can be used. Among the mineral particles, layered organic clay is more preferred. Layered organic clay refers to a substance in which organic onium ions are introduced between the layers of swelling clay. There is no restriction on the organic onium ions as long as they can be organically formed by utilizing the cation exchangeability of swelling clay. As mineral particles, when using layered organic clay minerals, the above-mentioned synthetic montmorillonite can be preferably used. Synthetic montmorillonite has the function of increasing the viscosity of the anti-glare layer forming composition, inhibiting the sedimentation of resin particles and inorganic particles, and thus adjusting the concavo-convex shape of the surface of the optical functional layer.

[0046] In order to cure the anti-glare layer forming composition by ultraviolet irradiation, a polymerization initiator can be added. As a polymerization initiator, a polymerization initiator that generates free radicals by ultraviolet irradiation can be used. As a polymerization initiator, free radical polymerization initiators such as acetophenone, benzophenone, thioxanthone, benzoin, benzoin methyl ether, and acylphosphine oxide can be used. As a polymerization initiator, for example, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, bis (2,4,6-trimethylbenzoyl) phenyl phosphine oxide, 2,2-diethoxy acetophenone, 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxyphenyl acetophenone, benzyl, benzoin, benzoin methyl ether, benzoin ethyl ether, p-chlorobenzophenone, p-methoxybenzophenone, Michler's ketone, acetophenone, 2-chlorothioxanthone, etc. can be used. One of them can be used alone, or two or more can be used in combination.

[0047] In addition, in the anti-glare layer forming composition, as a component (slip improver) that improves slip, preferably antifouling agent, leveling agent, oil repellent, water repellent, fingerprint adhesion preventing agent are added. As the above-mentioned additive, preferably fluorine-containing compound or silicone compound can be used. By adding the compound showing slip in the anti-glare layer 3 that becomes the outermost layer, slip can be further improved. In addition, various additives such as antistatic agent, defoamer, antioxidant, ultraviolet absorber, infrared absorber, colorant, light stabilizer, inhibitor, photosensitizer, etc. can also be added as needed.

[0048] Furthermore, as required, a solvent may be added to the anti-glare layer forming composition. As the solvent, one or more of the following may be used: alcohols such as methanol, ethanol, 1-propanol, 2-propanol, butanol, isopropanol, and isobutanol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ketone alcohols such as diacetone alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; glycols such as ethylene glycol, propylene glycol, and hexylene glycol; glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, diethyl cellosolve, diethyl carbitol, and propylene glycol monomethyl ether; esters such as methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, and amyl acetate; ethers such as dimethyl ether and diethyl ether; N-methylpyrrolidone, dimethylformamide, and the like, or a mixture of two or more thereof.

[0049] Figure 2 This is a cross-sectional view schematically showing another example of the optical film according to the embodiment.

[0050] The optical laminate 12 includes a transparent support 2, an anti-glare layer 3 laminated on one surface of the transparent support 2, and a low refractive index layer 4 (LR layer) laminated on the surface of the anti-glare layer 3. The optical laminate 12 is an optical film (also called "AGLR film") that suppresses the reflection and reflection of external light by scattering and optical interference of incident light generated by fine concavoconvexities on the outermost surface.

[0051] The low refractive index layer 4 has a refractive index lower than that of the anti-glare layer 3 as the underlying layer, and is a functional layer for suppressing reflection by optical interference.

[0052] The low refractive index layer 4 can be formed by coating a composition containing an active energy ray-curable compound on the surface of the anti-glare layer 3 and curing the coating. The low refractive index layer 4 may contain low refractive index fine particles in order to adjust the refractive index.

[0053] As low refractive index particles, for example, particles such as LiF, MgF, 3NaF·AlF or AlF (all with a refractive index of 1.4), or Na3AlF6 (cryolith, with a refractive index of 1.33), and silica particles with voids inside can be preferably used. The silica particles with voids inside are beneficial to the low refractive index of the low refractive index layer 4 because the part of the void is set to the refractive index of air (about 1). Specifically, porous silica particles and shell structure silica particles can be used. In addition, low refractive index particles are not necessary. When the refractive index of the active energy ray-curable compound after curing is lower than the refractive index of the anti-glare layer 3, the low refractive index particles can also be omitted.

[0054] As the active energy ray-curable compound, the polymerizable compound described in the anti-glare layer can be used. In addition, the above-mentioned polymerization initiator or solvent can be appropriately added to the low refractive index layer forming composition.

[0055] Since low refractive index layer 4 is the functional layer that becomes the most superficial layer, it is preferred to add antifouling agent, leveling agent, oil repellent, water repellent, fingerprint adhesion preventing agent as the component (slipping improving agent) that improves slipping property in the low refractive index layer forming composition. As the above-mentioned additive, fluorine-containing compound or silicone compound can be preferably used. In addition, various additives such as antistatic agent, defoamer, antioxidant, ultraviolet light absorber, infrared absorber, colorant, light stabilizer, inhibitor, photosensitizer etc. can also be added as required.

[0056] Between the transparent support 2 and the anti-glare layer 3, one or more hard coating layers, high refractive index layers, medium refractive index layers, antistatic layers, electromagnetic wave blocking layers, infrared absorption layers, ultraviolet absorption layers, color correction layers and other functional layers may be stacked.

[0057] The coating method of the above-mentioned anti-glare layer forming composition and low refractive index layer forming composition is not particularly limited, and can be coated using, for example, a spin coater, a roll coater, a reverse roll coater, a gravure coater, a micro gravure coater, a knife coater, a rod coater, a wire rod coater, a die coater, a dip coater, a spray coater, an applicator, etc.

[0058] Here, the details of the surface uneven shape of the optical laminate of the present embodiment will be described.

[0059] The uneven shape of the outermost surface of the optical functional laminate of the present embodiment simultaneously satisfies the following conditions (1) to (3).

[0060] 20,000 ≤ A ≤ 300,000 (1)

[0061] 300 ≤ B ≤ 800 (2)

[0062] 10 ≤ C ≤ 180 (3)

[0063] Here, A, B, and C are values derived by performing a fast Fourier transform (hereinafter referred to as "FFT") on the image data generated from the measurement data of the uneven height of the surface of the optical laminate, and calculating from the spatial frequency f in a specified range of the transformed image (power spectrum image). A is the average value of the power spectrum intensity in the range of 0 < f ≤ 100 cycle / mm, B is the average value of the power spectrum intensity in the range of 100 cycle / mm < f ≤ 200 cycle / mm, and C is the average value of the power spectrum intensity in the range of 200 cycle / mm < f ≤ 300 cycle / mm.

[0064] The calculation methods of the above values of A, B, and C are as follows.

[0065] First, three-dimensional data of the uneven height of the outermost surface of the optical laminate is obtained by measurement. The three-dimensional data of the uneven height includes the position within the measurement surface and the height of the unevenness. The three-dimensional data of the uneven height of the outermost surface can be measured by an optical interference method or a contact method. The obtained three-dimensional data is transformed into an image (first image) with the uneven height as the pixel value. Then, the first image is subjected to FFT to obtain an image after FFT processing (second image). Then, the X coordinate of the power spectrum in a specified range within the second image after FFT processing is transformed into the spatial frequency f. The average value of the true numbers of the power spectrum intensities in the ranges of 0 < f ≤ 100 cycle / mm, 100 cycle / mm < f ≤ 200 cycle / mm, and 200 cycle / mm < f ≤ 300 cycle / mm is calculated from the obtained spatial frequency and used as the above values of A, B, and C.

[0066] In the past, in order to show sliding properties, the outermost layer generally contains components such as fluorine compounds or silicone compounds that improve sliding properties, but only adding components that show sliding properties can only improve sliding properties to a limited extent. The inventors of the present application and others have conducted research and found that not only the outermost material and components contained, but also the surface concave-convex shape affect sliding properties. In addition, the inventors of the present application and others have studied the concave-convex shape that can improve sliding properties and found that the power spectrum intensity near the spatial frequency of 50cycle / mm has a great relationship with sliding properties. The higher the power spectrum intensity near the spatial frequency of 50cycle / mm (i.e., the higher the concave-convex height), the more the sliding properties are improved.

[0067] Sliding property can be represented by the size of friction coefficient. When the materials are the same, the friction coefficient is proportional to the contact area. The larger the contact area, the larger the friction coefficient. Here, the relationship of friction coefficient μ = friction force F / load (vertical load) N = contact area × shear stress / load N holds true. In addition, the shear stress depends on the material, and the load depends on the test conditions. Therefore, it is believed that the contact area between the ridges of the fingerprint and the convex part of the surface when the finger is placed on the surface of the optical laminate, and the change in contact area caused by the shear deformation of the finger in the sliding state affect the sliding property. The concave-convex shape that meets the above conditions (1) to (3) can reduce the contact area between the finger and the convex part of the surface when it is in contact with the finger and in the static state and the sliding state, resulting in improved sliding property.

[0068] The outermost surfaces of the optical laminates 11 and 12 preferably have a dynamic friction coefficient of 0.3 or less. If the dynamic friction coefficient of the outermost surfaces is 0.3 or less, the finger can slide smoothly when the image display device is subjected to a sliding operation such as tapping or swiping, and the usability is good.

[0069] The optical layered bodies 11 and 12 of this embodiment have excellent slidability because the outermost surface irregularities satisfy the above conditions (1) to (3). In addition, the slidability can be further improved by adding a slidability-enhancing component to the outermost functional layer.

[0070] The values ​​of A to C can be controlled by adjusting the particle size or amount of the filler added to the anti-glare layer 3 , the amount of additives, the film thickness of the anti-glare layer 3 , and the aggregation state of the filler during the film forming process.

[0071] The optical laminates 11 and 12 of this embodiment can be attached to the outermost surface of an image display panel such as a liquid crystal panel or an organic EL panel to form an image display device. A touch panel can also be provided between the optical laminates 11 and 12 and the image display panel. The optical laminates 11 and 12 of this embodiment have excellent sliding properties and are therefore suitable as optical films provided on the outermost surface of an image display device.

[0072] Example

[0073] Hereinafter, embodiments for implementing the present invention will be described.

[0074] (Example 1)

[0075] The following hardcoat (HC) compositions were prepared.

[0076] (HC composition 1: for forming an anti-glare layer)

[0077] Organic fine particles having an average particle size of 3.5 μm (SSX-2035 manufactured by Techpolymer) were dispersed in toluene using a paint shaker for 40 minutes, and then 5.0 parts by mass of the organic fine particles, 92.0 parts by mass of a condensate of pentaerythritol and acrylic acid represented by the following formula (Viscoat #300 manufactured by Osaka Organic Chemical Industry Co., Ltd., hereinafter referred to as "PETA"), and 3.0 parts by mass of a photopolymerization initiator (Omnirad 184 manufactured by IGM Resins BV) were mixed into toluene. The total solid content concentration in the composition was adjusted to 50% by mass. The mixture was stirred for 50 minutes using a paint shaker to prepare HC composition 1.

[0078] [Chemistry 1]

[0079]

[0080] (HC composition 2: for forming a low refractive index layer)

[0081] 45.0 parts by mass of PETA (Viscoat #300 manufactured by Osaka Organic Chemical Industry Co., Ltd.), 50.0 parts by mass of isopropyl alcohol-dispersed hollow silica fine particles having an average particle size of 75 nm in terms of solid content, 3.0 parts by mass of a photoinitiator for UV curing photopolymerization initiator, and 2.0 parts by mass of a fluorine-based antifouling agent (KY-1203 manufactured by Shin-Etsu Chemical Co., Ltd.) were added and mixed in isopropyl alcohol so that the total solid content concentration became 3.5% by mass, and the mixture was stirred for 50 minutes with a paint shaker to prepare HC composition 2.

[0082] Next, a 60 μm thick triacetyl cellulose (TAC) film (manufactured by Fujifilm, TJ40) was used as a transparent support. HC composition 1 was applied to one surface of the transparent support by a bar coater and dried at 100° C. for 1 minute in a dryer. A high-pressure mercury UV device was used in a nitrogen atmosphere (oxygen concentration was 500 ppm or less) so that the cumulative exposure amount reached 200 mJ / cm 2 The coating film was irradiated with ultraviolet rays in a manner to cure the coating film to form an anti-glare layer. In addition, the coating amount of the HC composition 1 was adjusted so that the film thickness after curing was 5 μm.

[0083] Next, HC composition 2 was applied on the antiglare layer using a bar coater and dried in a dryer at 100°C for 1 minute. A high-pressure mercury UV device was used in a nitrogen atmosphere (oxygen concentration was 500 ppm or less) to obtain a cumulative exposure of 200 mJ / cm 2 The coating film was irradiated with ultraviolet rays in a manner to cure the coating film to form a low refractive index layer. In addition, the coating amount of the HC composition 2 was adjusted so that the optical film thickness nd (nd = refractive index n × film thickness d (nm)) after curing was 550 / 4nm.

[0084] (Example 2)

[0085] An optical layered body was produced in the same manner as in Example 1 except that the low refractive index layer was not formed.

[0086] (Example 3)

[0087] An optical layered body was prepared in the same manner as in Example 1, except that the dispersion time of the organic fine particles in HC composition 1 by the paint shaker and the stirring time of the coating liquid were both set to 70 minutes.

[0088] (Example 4)

[0089] An optical layered body was prepared in the same manner as in Example 1 except that the dispersion time of the organic fine particles in the HC composition 1 by the paint shaker was changed to 70 minutes.

[0090] (Example 5)

[0091] An optical layered body was produced in the same manner as in Example 1 except that the organic fine particles in HC composition 1 were changed to 4.0 parts by mass of organic fine particles having an average particle diameter of 3.0 μm (SSX-103 manufactured by Techpolymer) and the blending amount of PETA was changed to 93.0 parts by mass.

[0092] (Example 6)

[0093] An optical layered body was produced in the same manner as in Example 5 except that the low refractive index layer was not formed.

[0094] (Example 7)

[0095] An optical layered body was prepared in the same manner as in Example 1 except that the coating amount of the HC composition 1 was changed so that the film thickness after curing would be 6.0 μm.

[0096] (Example 8)

[0097] An optical layered body was produced in the same manner as in Example 7 except that the low refractive index layer was not formed.

[0098] (Comparative Example 1)

[0099] An optical layered body was prepared in the same manner as in Example 1 except that the coating amount of the HC composition 1 was changed so that the film thickness after curing would be 4.5 μm.

[0100] (Comparative Example 2)

[0101] An optical layered body was prepared in the same manner as in Example 1 except that the coating amount of the HC composition 1 was changed so that the film thickness after curing would be 8.0 μm.

[0102] (Comparative Example 3)

[0103] An optical layered body was prepared in the same manner as in Example 1 except that the organic fine particles in the HC composition 1 were changed to organic fine particles having an average particle diameter of 5.0 μm (manufactured by Techpolymer, SSX-105).

[0104] (Comparative Example 4)

[0105] An optical layered body was prepared in the same manner as in Example 1 except that the organic fine particles in the HC composition 1 were changed to organic fine particles having an average particle diameter of 2.5 μm (SSX-102 manufactured by Techpolymer).

[0106] (Comparative Example 5)

[0107] An optical layered body was produced in the same manner as in Example 1 except that the blending amount of PETA in the HC composition 1 was 90.0 parts by mass and the blending amount of organic fine particles (SSX-2035 manufactured by Techpolymer) was 7.0 parts by mass.

[0108] (Comparative Example 6)

[0109] An optical layered body was produced in the same manner as in Example 1 except that the blending amount of PETA in the HC composition 1 was 94.0 parts by mass and the blending amount of the organic fine particles was 3.0 parts by mass.

[0110] (Comparative Example 7)

[0111] An optical layered body was prepared in the same manner as in Example 1 except that the dispersion time of the organic fine particles in the HC composition 1 by the paint shaker was changed to 20 minutes.

[0112] (Comparative Example 8)

[0113] An optical layered body was produced in the same manner as in Comparative Example 7 except that the low refractive index layer was not formed.

[0114] (Comparative Example 9)

[0115] An optical layered body was prepared in the same manner as in Example 1 except that the dispersion time of the organic fine particles in HC composition 1 by the paint shaker and the stirring time of the coating liquid were changed to 80 minutes.

[0116] (Comparative Example 10)

[0117] An optical layered body was produced in the same manner as in Comparative Example 9 except that the low refractive index layer was not formed.

[0118] The optical layered bodies of the respective Examples and Comparative Examples were evaluated as follows.

[0119] <Evaluation 1: Surface irregularities>

[0120] (Acquisition of three-dimensional data)

[0121] The three-dimensional data of the concavo-convex shape of the outermost surface of the optical laminate was measured by optical interference using Vertscan (Ryoka Systems, R3300H Lite). The measurement conditions were as follows: The concavo-convex height was based on the lowest position in the measurement range.

[0122] Camera model: Sony HR-50 1 / 3

[0123] Objective lens magnification: 5XTI

[0124] ·Eyepiece: 1X

[0125] Zoom lens: 1X

[0126] Light source: 530white

[0127] Wavelength filter: 520nm

[0128] ·Measurement equipment: Piezoelectric

[0129] ·Measurement mode: Phase

[0130] Scanning speed: 4μm / sec

[0131] Scanning range: 10μm~-10μm

[0132] · Number of effective pixels: 0%

[0133] · Measurement range: 940.8μm×705.6μm, 640pixel×480pixel

[0134] XY resolution: 1 pixel 1.47 μm

[0135] (FFT analysis)

[0136] FFT analysis was performed using the free software "ImageJ 1.53h" in the Windows (registered trademark) 10 environment. The steps are as follows.

[0137] 1. Transform the three-dimensional data into TIFF image data with height as the pixel value.

[0138] 2. Perform FFT with reference to the original three-dimensional data values (measured values of height). The image size after FFT processing is set to 1024 pixel × 1024 pixel.

[0139] 3. Perform processing on the image after FFT to restore the power spectrum intensity to the measured value.

[0140] 4. In the processed image, specify the range of ±20 pixel on the positive X-axis passing through the origin, and output the power spectrum intensity.

[0141] 5. Transform the X coordinate of the output power spectrum into the spatial frequency f according to the pixel size of the original three-dimensional data.

[0142] 6. Calculate the average value of the logarithm of the power spectrum intensity (values A to C) in each range of 0 < f ≤ 100 cycle / mm, 100 cycle / mm < f ≤ 200 cycle / mm, and 200 cycle / mm < f ≤ 300 cycle / mm based on the calculated spatial frequency.

[0143] <Evaluation 2: Optical properties>

[0144] The optical properties of the optical laminate are evaluated according to the following evaluation of haze, antiglare property, and reflectance, and according to the following criteria.

[0145] ◎: There is 1 or more evaluation of ◎ in haze, antiglare property, and reflectance, and the remaining evaluations are ○

[0146] ○: All evaluations of haze, antiglare property, and reflectance are ○

[0147] ×: There is 1 or more evaluation of × in haze, antiglare property, and reflectance

[0148] (Haze)

[0149] The haze is measured using a haze meter (NDH7000, manufactured by Nippon Denshoku Industries Co., Ltd.) according to the haze test method of the test method for optical properties of plastics JIS K 7136. The evaluation criteria for optical properties are as follows.

[0150] ◎: The haze is 6% or more and less than 8%

[0151] ○: The haze is 4% or more and less than 6%, or 8% or more and less than 10%

[0152] ×: Haze is less than 4% or more than 10%

[0153] (Anti-glare)

[0154] Figure 3 is a diagram showing the evaluation method of anti-glare properties, Figure 4 It is a figure which shows the evaluation example of anti-glare property.

[0155] The obtained optical laminate was bonded to a blackboard using an optical adhesive in such a manner that the functional surface was the surface. In addition, a three-wavelength fluorescent lamp and an optical laminate were arranged in such a manner that light was irradiated perpendicularly to the functional surface. The surface of the optical laminate was observed from a direction at 70° relative to a perpendicular line from the three-wavelength fluorescent lamp to the functional surface, where a line connecting the viewpoint and the image of the three-wavelength fluorescent lamp projected on the functional surface was observed, and the anti-glare property was evaluated according to the following criteria.

[0156] 0: The outline of the three-wavelength fluorescent lamp can be seen, but the edges are blurred.

[0157] ×: The outline of the three-wavelength fluorescent lamp is too blurry to be seen, or the edge is clearly visible

[0158] (Reflectivity)

[0159] The spectral reflectance of the functional layer surface of the obtained optical laminate at an incident angle of 5° was measured using an automatic spectrophotometer (U-4100, manufactured by Hitachi, Ltd.) and evaluated according to the following criteria. During the measurement, a matte black coating was applied to the back side of the TAC film (the side without the functional layer formed) to perform an anti-reflection treatment.

[0160] ◎:Reflectivity less than 0.5%

[0161] ○: Reflectivity is 0.5% or more and less than 1%

[0162] ×: Reflectivity is 1% or more

[0163] <Evaluation 3: Sliding property>

[0164] The dynamic friction coefficient of the functional layer surface of the obtained optical layered body was measured in accordance with JIS K 7125. The measuring apparatus and measuring conditions are as follows.

[0165] ·Evaluation device: Static and dynamic friction tester TL201Tt (manufactured by Trinity-Lab Co., Ltd.)

[0166] Probe selection: Tactile contact head with fingerprint pattern (proposed by Maeno Takashi's laboratory at Keio University's Graduate School of System Design and Management and Nomura Misune's laboratory at Yamagata University's Graduate School of Science and Engineering)

[0167] Analysis software: Tribology analysis software

[0168] Vertical load: 20g

[0169] Sliding speed: 10mm / sec

[0170] Moving distance: 30mm

[0171] Data collection speed: 1msec

[0172] The obtained optical laminate was bonded to a blackboard using an adhesive so that the functional surface was the surface. The sample was fixed on the table of the evaluation device, and the friction coefficient between the tactile contact head with a fingerprint pattern and the functional surface was measured and analyzed according to the above conditions. The average value of the friction coefficient in the sliding state (movement distance between 10mm and 20mm) was calculated, and the obtained value was used as the dynamic friction coefficient μk, and evaluated according to the following criteria.

[0173] ○: μk≤0.3

[0174] ×: 0.3<μk

[0175] Table 1 shows the evaluation results.

[0176] Table 1

[0177] LR A B C Optical properties Sliding Example 1 have 298,976 799 175 ◎ ○ Example 2 none 253,847 715 173 ○ 〇 Example 3 have 215,149 395 87 ◎ ○ Example 4 have 273,890 680 142 ◎ 〇 Example 5 have 89,576 368 31 ◎ ○ Example 6 none 90,357 364 35 ○ 〇 Example 7 have 46,346 325 161 ◎ 〇 Example 8 none 46,854 442 45 〇 〇 Comparative Example 1 have 1,109,594 4,522 514 × ○ Comparative Example 2 have 7,011 52 4 × × Comparative Example 3 have 482,245 672 104 × ○ Comparative Example 4 have 13,664 556 49 〇 × Comparative Example 5 have 268,456 1,423 124 × 〇 Comparative Example 6 have 53,557 172 45 〇 × Comparative Example 7 have 252,548 714 385 〇 × Comparative Example 8 none 255,462 724 402 × × Comparative Example 9 have 218,224 388 5 〇 × Comparative Example 10 none 232,469 315 7 × ×

[0178] As shown in Table 1, in the optical layered bodies of Examples 1 to 8, A to C satisfied the conditions (1) to (3), and were excellent in both optical properties and slidability.

[0179] On the other hand, in the optical layered bodies of Comparative Examples 1 to 10, at least one of A to C did not satisfy the above conditions, and one or both of the optical characteristics and the slidability were evaluated low.

[0180] From the above, it was confirmed that an optical layered body excellent in optical properties and slidability can be realized by making the above-mentioned A to C satisfy the conditions (1) to (3) simultaneously.

[0181] Industrial Applicability

[0182] The present invention can be used as an optical film provided on the outermost surface of an image display device.

[0183] Explanation of symbols

[0184] 1. Optical laminate

[0185] 2Transparent support

[0186] 3 Anti-glare layer

[0187] 4 Low refractive index layer

Claims

1. An optical laminate, characterized in that: The optical layered body has a concavoconvex shape on the outermost surface and satisfies the following conditions (1) to (3) at the same time. 20,000≤A≤300,000 (1) 300≤B≤800 (2) 10≤C≤180 (3) In which, the three-dimensional data of the concavo-convex height obtained by measuring the concavo-convex shape by an optical interference method or a contact method is transformed into the first image data with the concavo-convex height as a pixel value, and the first image data is transformed into the second image by fast Fourier transform, and the spatial frequency f of the X coordinate of the power spectrum of the image in the second image passing through the origin and in the range of ±20 pixels on the positive X axis and the Y axis direction is calculated, A: The average value of the power spectrum intensity in the range of 0<f≤100cycle / mm, B: The average value of the power spectrum intensity in the range of 100cycle / mm<f≤200cycle / mm, C: Average value of the power spectrum intensity in the range of 200 cycle / mm<f≤300 cycle / mm.

2. The optical layered body according to claim 1, wherein: The coefficient of dynamic friction of the outermost surface of the optical layered body is 0.3 or less.

3. The optical laminate according to claim 1, wherein: The optical layered body includes a transparent support and a first functional layer laminated on at least one surface of the transparent support, wherein the concavo-convex shape of the outermost surface is formed by the first functional layer.

4. The optical layered body according to claim 2, wherein: A second functional layer having a refractive index lower than that of the first functional layer is provided on the first functional layer.

5. The optical layered body according to claim 2, wherein: The first functional layer contains a fluorine-containing compound or a silicone compound.

6. The optical layered body according to claim 3, characterized in that: The second functional layer contains a fluorine-containing compound or a silicone compound. 7 . An image display device comprising the optical layered body according to claim 1 .